The Relative Impacts of Economics Journals: 1970-1990 - Laband, David N.; Piette, Michael J. (Journal of Economic Literature, 1994)
Our data collection and database assembly efforts were assisted by John P. Sophocleus, Mark Gwartney, Michele Butler, and Scott Ralston. We received extremely valuable computer programming assistance from Jon Brunson and Edward Novak. Constructive comments were receivedfrom two anonymous reviewers. Financial supportfrom the Faculty Development Committee at Salisbury State University is gratefully acknowledged.